Evaluación docente para la mejora continúa - Topa Pérez, Carmen Narcisa (2017)
This research aims to investigate the epistemological foundations of the different processes of teacher evaluation and how it influences the continuous improvement of education as well as aspects associated with teaching and learning, in addition to disseminating existing information and favoring all the members of the educational community, to incorporate the teaching evaluation as established by the Ministry of Education through the National Institute of Educational Evaluation (INEVAL), as an aspect of knowledge and level of professional preparation of teachers in a way that allows the progress of learning is permanent in students. The population that has been taken into account in the present investigation is the managers, teachers and students of the middle level of Ana Páez Educative Unit….